Fifteen-minute consultation: A structured approach to the management of stroke in a child. Issue 1 (19th June 2020) - O'Reilly, Ailva; McCullagh, Gary
Abstract : Childhood stroke is a rare but important diagnosis. Even though most children with stroke are ultimately cared for by specialist multidisciplinary paediatric neurology teams, their initial presentation will have been to a general paediatric admissions team. Assessing and managing children who present with stroke in the general paediatric setting can be challenging due to wide variation in its clinical features and underlying aetiologies. Despite the clarity provided by the Royal College of Paediatrics and Child Health recommendations which were published in 2017, many paediatricians still feel ill-prepared when assessing these high-risk patients. This article aims to provide an informative and structured approach to the assessment and management of children with stroke.